Long Term Follow up of Young People With Chronic Fatigue Syndrome Attending a Pediatric Outpatient Service - Rowe, Katherine S. (Frontiers in Pediatrics, 2019)
Objective: To describe the functional and educational long-term outcomes, predictive factors for recovery and feedback regarding management in pediatric/adolescent myalgic encepahalomyelitis/chronic fatigue syndrome (ME/CFS). Methods: Seven hundred and eighty four young people, mean age 14.6 (6-18) years, with ME/CFS diagnosed at a specialist pediatric hospital and receiving regular care, were followed up for a mean 8 (range 1-21) years after onset. A study group of 418 provided baseline symptoms, history, depression, anxiety and General Health questionnaires and repeated follow up questionnaires. The remaining 366, without similar standardized baseline information, were followed up as a comparison group. Functional rating and questionnaire information was requested regarding persistent symptoms, level of functioning, duration of illness if recovery was reported, social engagement and school/work attendance. Feedback regarding useful information, helpful interventions or personnel, alternative medicine use, support services and ways management could be improved was also sought. Results: Follow up data were returned from 81.8% (87.1% of study group and 75.6% of comparison group). The reported mean duration of illness was 5 (range 1-15) years in the 50% who reported recovery. By 5 years 38% reported recovery and by 10 years 68% reported recovery. At 10 years the mean functional score was 8/10 (range 2-10) with 5% scoring <6. Depression or anxiety at diagnosis was not predictive of non-recovery. Designing and monitoring their own management plan that included educational, social, physical and enjoyable activities, as well as having symptom management and understanding professionals were highly valued. However, remaining engaged in an education system that flexibly accommodated their illness and aspirations was consistently reported as crucial for long term functioning. Conclusions: ME/CFS in young people has a mean duration of 5 years (1-15) with 68% reporting recovery by 10 years. All improved functionally with 5% remaining very unwell and a further 20% significantly unwell. There were no obvious predictors for recovery such as anxiety, depression or illness severity at baseline. However, depression, anxiety, orthostatic intolerance and to a lesser extent pain at follow up were identified as hampering recovery or function. Supportive professionals, remaining engaged in education and management strategies were identified as helpful.